2018
DOI: 10.1590/0103-1104201811611
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos dos programas governamentais e da fecundidade sobre a mortalidade infantil do Semiárido brasileiro

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…In the Brazilian semiarid, the Bolsa Família Program, allied to the FHS, significantly reduced infant mortality and total fertility rates. 17 In the state of São Paulo, between 1998 and 2009, FHS coverage above 50% showed a protective effect in relation to post-neonatal mortality, and coverage of up to 50% or higher were protective factors for hospitalizations for pneumonia in children under 1 year. The authors also concluded that the effectiveness of the FHS on child health outcomes may vary, due to local and regional contexts.…”
Section: Discussionmentioning
confidence: 95%
“…In the Brazilian semiarid, the Bolsa Família Program, allied to the FHS, significantly reduced infant mortality and total fertility rates. 17 In the state of São Paulo, between 1998 and 2009, FHS coverage above 50% showed a protective effect in relation to post-neonatal mortality, and coverage of up to 50% or higher were protective factors for hospitalizations for pneumonia in children under 1 year. The authors also concluded that the effectiveness of the FHS on child health outcomes may vary, due to local and regional contexts.…”
Section: Discussionmentioning
confidence: 95%
“…Um incremento de 10% da cobertura de saúde da família implicaria, por exemplo, em redução de 4,5% da mortalidade infantil 21 . Recentemente, estudo conduzido no semiárido brasileiro mostrou impacto positivo da ESF na redução da mortalidade de crianças, produto da ampliação do acesso a serviços de qualidade para as famílias adstritas 22 . O cenário de luta pela consolidação do Sistema Único de Saúde (SUS) ganhou novo fôlego com a implementação da Política Nacional de Atenção Básica (PNAB) em 2006, e reformulada em 2011 e 2017.…”
Section: Discussionunclassified
“…A análise dos primeiros cinco anos do PBF mostrou uma diminuição de 9,3% da mortalidade infantil 18 . Resultados semelhantes foram relatados em estudo no semiárido brasileiro 22 .…”
Section: /107unclassified
“…No âmbito das políticas de saúde que influenciaram de maneira decisiva a redução da TMI destaca-se a Política Nacional de Atenção Integral à Saúde da Criança (PNAISC), publicada em 2015. O PNAISC trouxe como prioridade a promoção do aleitamento materno e proteção à saúde da criança, buscando orientar os gestores e profissionais da saúde sobre as ações voltadas para esta população e favorecendo a organização do processo de trabalho para melhor atende-las, desde a concepção até os nove anos de vida (5) as crianças (2)(3)(4)(5)6) .…”
Section: A Significativa Redução Da Mortalidadeunclassified